Agency Costs, Ownership, And Internal Governance Mechanisms: Evidence From Chinese Listed Companies - Vijayakumaran, R. (Asian Economic and Financial Review, 2019)
In recent years, there has been an increasing interest in assessing the effectiveness of corporate governance in China. This paper examines the impact of internal governance mechanisms such as ownership structure and board characteristics and debt financing on agency costs making use of a large panel of Chinese listed firms. We find that managerial ownership and debt financing work as effective corporate governance mechanisms for Chinese listed firms to mitigate agency conflicts and the resultant agency costs.
Keywords: Agency costs; Ownership structure; Board structure; Debt financing